Impact of Definitive Chemoradiation on Quality-of-Life Changes for Patients With Anal Cancer: Long-term Results of a Prospective Study. Issue 5 (6th April 2022) - Hosni, Ali; Ringash, Jolie; Han, Kathy; Liu, Zhihui (Amy); Brierley, James D.; Wong, Rebecca K.S.; Dawson, Laura A.; Cummings, Bernard J.; Krzyzanowska, Monika K.; Chen, Eric X.; Hedley, David; Knox, Jennifer J.; et al.
Abstract : BACKGROUND: Maintaining and improving quality of life (QOL) are important goals of anal cancer management. This disease is generally curable, with many long-term survivors. OBJECTIVE: Long-term QOL after chemoradiation for patients with anal cancer was evaluated. DESIGN: This was a prospective cohort study. SETTINGS: This study used data from a prospective study of patients with anal cancer who were treated with chemoradiation between 2008 and 2013. PATIENTS: Patients with anal cancer who were treated with image-guided intensity-modulated radiation therapy were included. INTERVENTIONS: English-speaking patients completed European Organization for Research and Treatment of Cancer cancer-specific (C30) and site-specific (CR29) QOL questionnaires at baseline, at end of radiation, at 3 and 6 months, and then annually. MAIN OUTCOMES MEASURES: Long-term QOL was evaluated clinically (a change in score of ≥10 points was considered clinically significant) and statistically (using repeated-measurement analysis) by comparing the subscale scores at 1, 2, and 3 years with baseline scores. Subanalysis compared patients who received a radiation dose of 45 to 54 Gy versus 63 Gy. RESULTS: Ninety-six patients were included (median follow-up of 56.5 months). The symptom and functional scales showed a clinically significant decline at the end of treatment with improvement by 3 months after treatment. There was a long-term statistically significant decline in dyspnea, body image, bowel embarrassment, fecal incontinence, and hair loss, and there was long-term statistically and clinically significant worsening of impotence. Higher radiation dose (63 Gy) was not associated with significantly worse QOL. LIMITATIONS: Limitations included single-institution, single-arm study design, and lack of dose reconstruction (ie, analyses were based on prescribed, rather than delivered, dose). CONCLUSIONS: Patients with anal cancer treated with chemoradiation reported recovery of overall QOL to baseline levels. Specific symptoms remained bothersome, emphasizing the need to address and manage the chemoradiation-induced symptoms, during treatment and in the long term. See Video Abstract at http://links.lww.com/DCR/B905 . IMPACTO DE LA QUIMIORRADIACIÓN DEFINITIVA EN CAMBIOS EN LA CALIDAD DE VIDA DE LOS PACIENTES CON CÁNCER ANAL: RESULTADOS A LARGO PLAZO DE UN ESTUDIO PROSPECTIVE: ANTECEDENTES: Mantener y mejorar la calidad de vida son objetivos importantes del tratamiento del cáncer anal, ya que esta enfermedad generalmente es curable, con muchos sobrevivientes a largo plazo. OBJETIVO: Se evaluó la calidad de vida a largo plazo después de la quimiorradiación en pacientes con cáncer anal. DISEÑO: Este fue un estudio de cohorte prospectivo. ENTORNO CLINICO: Utilizamos datos de un estudio prospectivo en pacientes con cáncer anal tratados con quimiorradiación entre 2008-2013. PACIENTES: Los pacientes con cáncer anal fueron tratados con radioterapia de intensidad modulada guiada por imágenes. INTERVENCIONES: Los pacientes de habla inglesa completaron los cuestionarios de calidad de vida específicos de cáncer (C30) y específicos del sitio (CR29) de la Organización Europea para la Investigación y el Tratamiento del Cáncer al inicio, al final de la radiación, 3 y 6 meses, y luego anualmente. PRINCIPALES MEDIDAS DE RESULTADOS: Se evaluó a largo plazo la calidad de vida clínicamente (un cambio en la puntuación de ≥10 puntos se consideraron clínicamente significativo) y estadísticamente (usando análisis de medición repetida) comparando las subescalas de puntuación al 1, 2, y 3 años. Con puntuaciones de referencia. El subanálisis comparó pacientes que recibieron 45–54 Gy versus 63 Gy. RESULTADOS: Se incluyeron un total de 96 pacientes (mediana de seguimiento: 56, 5 meses). La mayoría de las escalas funcionales y de síntomas mostraron una disminución clínicamente significativa al final del tratamiento con una mejoría a los 3 meses posteriores al tratamiento. Hubo una disminución estadísticamente significativa a largo plazo en disnea, imagen corporal, vergüenza intestinal, incontinencia fecal y pérdida de cabello; y hubo un empeoramiento a largo plazo estadística y clínicamente significativo en impotencia. La dosis de radiación más alta (63 Gy) no se asoció con una calidad de vida significativamente peor. LIMITACIONES: Institución única, diseño de estudio de un solo brazo y falta de recomposición de la dosis (es decir, los análisis se basan en la dosis prescrita, en lugar de la administrada). CONCLUSIÓNES: Los pacientes con cáncer anal tratados con quimiorradiación reportaron una recuperación de la QOL en general a los niveles de base. Síntomas específicos siguieron siendo molestos, lo que enfatiza la necesidad de resolver y tartar los síntomas inducidos por la quimiorradiación no solo durante el tratamiento, sino a largo plazo. Consulte Video Resumen en http://links.lww.com/DCR/B905 . (Traducción— Dr. Francisco M. Abarca-Rendon )